The Role of Hygiene Education in Forming Healthy Living Habits in Children - Haryani, Dini (Research of Service Administration Health and Sains Healthys, 2024)
Hygiene education plays an important role in forming healthy living habits from an early age. This study aims to explore the effectiveness of hygiene education in increasing hygiene awareness and practices among elementary school children. Using mixed methods, data was collected through questionnaire surveys and direct observation of 200 students in several elementary schools in XYZ City. The research results show that systematic and structured hygiene education can increase students' understanding of the importance of cleanliness and health. In addition, this research found that students who received regular hygiene education tended to have better healthy living habits compared to those who did not receive such education. These findings emphasize the importance of integrating hygiene education in the school curriculum to form a generation that is healthier and aware of the importance of cleanliness.